Coral bleaching monitoring using drone aerial photo in selected areas in Tioman Island, Pahang - Ahmad, Zuhairi; Kassim, Zaleha; Shammodin, Muhammad Shaheed; Ayob, Ahmad Faezal; Rosli, Muhammad Khairulanwar; Md. Rosli, Nur Suhaila; Hasnan, Hazwani Hanim (Jabatan Taman Laut Malaysia, Kementerian Air, Tanah dan Sumber Asli, 2018)
In 2016, coral reefs in the world experienced the biggest coral bleaching event ever recorded. As a result of the event, very large areas were bleached. Tioman Island was reported to experience the episodes of bleaching but the recovery process was not known. This research focused on the current state of corals in the island and to investigate the reliability of using a drone as unmanned aerial vehicle (UAV) for coral bleaching monitoring. The approach of the study was to use the low altitude aerial drone imagery for coral bleaching surveys in combination with Remote Sensing and GIS tools. Sampling sites were fixed at the Renggis, Soyak, Salang, Batu Malang and Tulai at the western part of the island which are known as hot spot for tourists. Bathymetry of the areas was determined and low altitude drone flights were made twice (morning and evening flight) at every site. Following the drone flight paths, three underwater transect lines were established at every site for underwater video recording. Data were analysed from the drone images and separation was made between coral cover, substrate and water (ISODATA). Marking of possible bleaching was done (based on the B band) using vector coral and Sequential Maximum Angle Convex Cone (SMACC). Results from underwater video analysis using Coral Point Count with Excel Extension (CPCe) were then compared with drone data. Highest sea surface temperature (SST) recorded in 2017 was 31 °C (in May) and lowest temperature was 27°C (in January) which was entirely lower than 2016. There is no significant effect of SST towards bleaching as monitored by CVT and drone in 2017 for all sampling stations. Most of the bleaching from August to October occurred in patches (compared to the whole area such as during 2016 bleaching).The hypothesis that results from drone methods has no difference than CVT for monitoring the patterns of coral bleaching was accepted at 4 stations and rejected at 2 stations. Conclusively, drone was successfully showed the bleaching points in the study area, thus the method is potentially contribute to the bleaching monitoring activities (reduce manpower; reduce cost over large coverage; for the purpose of ad-hoc monitoring; baselines study). If compared to satellite images, drone images may lack in suitable spectral for coral identification, but yet drone images allow continuous non-scheduled time for image acquisitions with high resolutions.